(untitled) (Journal of the College of Education for Women, 2019)
It is known that energy subiect has ocuppied a lot of scientests minds abouthow to treat the traditional energy and the renewing energy . we know thatmost traditional energy coal , oil , Natural gas, neuclear fuel , are limitedguantiy and alsow subjected to be ended .Statics studies refer to reserveof oil in world will exhausted btween ( 2075- 2100) and alsow cosl too .While neuclear fuerl which the world seek today through explod the uraniumatom ( 233) the therum atom (239) and neuclear mxied through ruemlearmixing , These energy have effect on environment and humanity speciaty ifthey are used in militery purposes .For all theses scientests srarch for resources of renewing enery throughresearches studies , using environment technology reduce traditional energy,they found that the resources of ernewing energy ( sun power , wind power ,mechanical power of water,chamical power of water , underland power,aidragyn power , natural power, laser power )The presnet study try to make suggestd plan to develop the resources oftraditional and contionuos energy and use them in arabic enviroment . Theresearcher found there is no plan for developing energy resources , he triedthrough this study to present infront of researchers and discuss the geogrphyteachers role who have the ability and srarch in natural resouces speciallythe resources of engery , through planning and developing these resourcesreaching to ( sustainable development ) which appear as a new concept fordevelopment and planning after 1997 by ( UN programm ) in developing theresources of humanity and nature and the right present and futuregeneration far away from ( poverty + ignorance + disease ) specially in arabicenviroment